Syphilis in Georgia, 2009-2014 - Kathryn Moore; Leonardo Parker; Joy Wells (Georgia Southern University, 2016)
Background: In the period of 2002-2014, Georgia has ranked among the top three states in the United States for rates of primary and secondary syphilis cases, creating a continuing need to analyze the data and to plan and implement disease prevention efforts. Methods: The present effort involved analysis of data from Georgia's electronic disease reporting system, State Electronic Disease Surveillance System (SendSS), including demographic characteristics by year for the period of 2009-2014 and behavioral data obtained from interviews with communicable disease specialists. Results: In Georgia, from 2009-2014, primary and secondary syphilis, the infectious stages of the disease, were seen most commonly among black, non-Hispanic (77%) males (91%) between the ages of 20-29 (45%); 52% were males who have sex with other males. Conclusions: Analysis of the data provides a better understanding of the populations affected by syphilis. It can enhance discussions about disease surveillance, prevention, and strategies to decrease the burden of this disease.